Lenteur et vision : l’empreinte du western dans le roman français contemporain - Elisa Bricco (Cahiers de Narratologie)
Beyond the rebound effect, where the movie enters into the literature by transposition of scriptural and composition techniques, we are now witnessing a true integration of cinema stylèmes and topoï in the novel. By a deep analysis of Patrick Chatelier’s Pas le bon pas le truand, we question this assimilation process that works the material of the text in terms of thematic and structural. The writer demonstrates attention to creative film structures and he uses it to compose his text. In rewriting a scene from a Sergio Leone film, he assimilates into his textual material two processes: the slowness with which the scenes are told in detail, and repeated so as to mimic the changes in visual perspective, the shot / reverse shot, and the primacy of the visual in the constructionof the narrative, which depicts a true balance between reality and film probability.